Peningkatan Kualitas Pada Proses Perakitan Sepatu Dengan Six Sigma - Dian F. Hidayat (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2016)
Six Sigma is a kind of system for increasing quality by using DMAIC method. The improvement step has been implemented from problem assessment until controlling of improvement result. This observation has been implemented in manufacturing industry, which produces sport shoes. This product is distributed in over many different countries across the world. And therefore, requires some efforts to keep implementing the improvement for increasing its quality in order the consumer trustworthy to the quality produced will be steady maintained. The purpose for this observation is for increasing the quality that is implemented within the manufacturing process by using six sigma. By using DMAIC improvement begins by determining the over cement at the define step, which is the main reason for the occurred problem. Then at the measure step, the improvement is using a method of measurement system analysis gage r & r studies and capability analysis, and further more it is analyze the factors which are affecting the reason of the problem. At the final step the improvement applying some trials by using design of experiment for improvement suggestions until controlling at the control step as final step of DMAIC. The result from those improvements has generated percentage increase within the production quality, an increase at sigma level, and reduced of height cement problem as a main problem of improvement.